Cross-Cultural Perspectives of English Language Teaching: A Comparative Case Study of Junior High Schools in Indonesia and The Philippines - Belgis Raya Bian Paradieshta; Irmayani Irmayani; Syifa Khuriyatuz Zahro; Lillian Durango Balbon (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
English Language Teaching (ELT) in Southeast Asia is situated at the intersection of global communication demands, curriculum reform, and culturally embedded pedagogical practices. Differences in language status and educational environments shape how communicative curricula are enacted. This study examines how cultural orientations influence ELT implementation in two junior high schools: SMPN 1 Lamongan in Indonesia and SLSU Laboratory Junior High School in Tomas Oppus, Philippines. Using a qualitative comparative case study design, data were collected through document analysis, semi-structured interviews with four English teachers, and classroom observations involving 70 students. Thematic analysis was conducted using Hofstede’s cultural dimensions, Byram’s intercultural communicative competence framework, and Tyler’s curriculum alignment model. Findings indicate that the interaction of language exposure, participation norms, and pedagogical structures shapes communicative practices. In the Indonesian classroom, communicative activities are implemented through teacher-guided scaffolding and collaborative tasks, reflecting hierarchical interaction patterns and limited English exposure. In contrast, the Philippine classroom demonstrates more sustained communicative interaction supported by extensive use of English and facilitative teaching practices. This study provides a context-sensitive account of how cultural orientations mediate communicative ELT practices and highlights the relationship between macro-cultural values and classroom-level pedagogy in Southeast Asia.